2009
DOI: 10.1002/eji.200838283
|View full text |Cite
|
Sign up to set email alerts
|

IL‐4 blocks M‐CSF‐dependent macrophage proliferation by inducing p21Waf1 in a STAT6‐dependent way

Abstract: Macrophages are recruited from the blood stream to the inflammatory loci to carry out their functional activities. In an early phase of the cell cycle, macrophages become activated by Th1-type cytokines (i.e. IFN-c), thereby producing several factors (cytokines, NO, etc.) and developing pro-inflammatory activities. When bacteria and apoptotic bodies are removed, through the interaction with Th2-type cytokines (i.e. IL-4), macrophages become anti-inflammatory and repair damaged tissues. Incubation of bone-marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 62 publications
6
31
0
Order By: Relevance
“…Intriguingly, the proliferation rate of macrophages treated simultaneously with M-CSF and IL-4 was 43% lower ( n  = 12 experiments; P <0.001) than that determined for macrophages treated with M-CSF alone (data not shown). These data are in agreement with Arpa and colleagues, who demonstrated an inhibition of M-CSF-stimulated proliferation by IL-4 due to induction of p21 Waf1 (Arpa et al, 2009). Similar to observations made on IL-4-stimulated macrophages, M-CSF-induced proliferation of macrophages was abolished by NS8593 ( n  = 9 experiments) or FTY720 ( n  = 9 experiments) (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Intriguingly, the proliferation rate of macrophages treated simultaneously with M-CSF and IL-4 was 43% lower ( n  = 12 experiments; P <0.001) than that determined for macrophages treated with M-CSF alone (data not shown). These data are in agreement with Arpa and colleagues, who demonstrated an inhibition of M-CSF-stimulated proliferation by IL-4 due to induction of p21 Waf1 (Arpa et al, 2009). Similar to observations made on IL-4-stimulated macrophages, M-CSF-induced proliferation of macrophages was abolished by NS8593 ( n  = 9 experiments) or FTY720 ( n  = 9 experiments) (Fig.…”
Section: Resultssupporting
confidence: 93%
“…It has been demonstrated that STAT6 is required to induce the expression of CD23 and MHC class II, IgE isotype switching in B cells [3], as well as differentiation of Th2 type T cells [4]. However, STAT6 blocks IL-4-dependent inhibition of IFN-γ-induced gene expression in macrophages or Th1 type T-cell differentiation, indicating that STAT6 plays a key role in negative regulation of gene expression [5,6]. Although little is known regarding the mechanisms of down-regulation of STAT6-dependent signaling, recent reports of STAT6 isoform with carboxyl-truncation in both bone marrow-derived mast cells and mast cell lines suggest that STAT6 could function as a dominant-negative regulator in gene expression, which, due to lack of the carboxyl-terminus, interferes with the normal ability of STAT6 to induce transcription of target genes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only 6% of the target genes in our RNAi data are reported to be regulated by STAT6, by using genome-wide screens performed either on T or B cells of Stat6 À/À mice or STAT6-RNAi experiments, or bound by STAT6 in electrophoretic mobility shift assay (EMSA) (Table S1) (Ahn et al, 2009;Arpa et al, 2009;Bü ttner et al, 2004;Chen et al, 2003;Filen et al, 2009;Gabay et al, 1999;Hebenstreit et al, 2003;Kim et al, 2006;Kurata et al, 1999;Lund et al, 2007;McGaha et al, 2003;Ohmori et al, 1996;Schaefer et al, 2001;Schrö der et al, 2002;Yang et al, 2005;Zhang et al, 2000;Zhu et al, 2002). In addition, few of the genes, such as MAOA, are suggested to be regulated by STAT6 by using indirect methods such as in silico predictions (Chaitidis et al, 2004).…”
Section: Immediate Target Genes Of Stat6mentioning
confidence: 97%